Induction of Pyruvate Dehydrogenase Kinase 1 by Hypoxia Alters Cellular Metabolism and Inhibits Apoptosis in Endometriotic Stromal Cells. (June 2019) - Lee, Hsiu-Chi; Lin, Shih-Chieh; Wu, Meng-Hsing; Tsai, Shaw-Jenq
Endometriosis is a common gynecological disease, which is defined as the growth of endometrial tissues outside the uterine cavity. It often causes dysmenorrhea, dyspareunia, chronic pelvic pain, and infertility in reproductive-age women. However, the pathogenesis of endometriosis remains largely unclear. Since our previous study revealed that ectopic endometriotic stromal cells experience greater hypoxic stress than their eutopic counterparts, we aim to investigate whether the metabolic properties are changed in the ectopic endometriotic stromal cell when compared to its eutopic counterpart. Here, we found the expression of pyruvate dehydrogenase kinase 1 (PDK1), a critical enzyme in regulating glucose metabolism, was increased in ectopic stromal cells. Molecular characterization reveals that overexpression of PDK1 is induced by hypoxia through transcriptional regulation. Upregulation of PDK1 in ectopic endometriotic stromal cells was accompanied by increases in lactate production and oxygen consumption rate when compared to eutopic endometrial stromal cells. Furthermore, our data showed that inhibition of PDK1 activity by treatment with dichloroacetate inhibits the lactate production and oxygen consumption rate of ectopic stromal cells. In addition, hypoxia-induced PDK1 expression prevented cells from H2 O2 - and low nutrient-induced cell death. These data indicate that ectopic endometriotic cells may adapt to hypoxic microenvironment via upregulating PDK1 and reprogramming metabolism, which provides a survival advantage in the hostile peritoneal microenvironment.